HOMEX: Persuasive Technology Acceptance Model and the Moderating Effect of Culture - Oyibo, Kiemute; Vassileva, Julita (Frontiers in Computer Science, 2020)
The number of fitness applications on the market is increasing annually, driven by the increasing awareness of the need to support and motivate physical activity to reduce the incidence of non-communicable diseases worldwide. However, there is limited research on the user-experience (UX) design attributes that drive their adoption and the moderating role culture plays. Consequently, we conducted a study on the Persuasive Technology Acceptance Model (PTAM) for a fitness application aimed at motivating physical activity at home. Using Canada (an individualist culture, n = 189) and Nigeria (a collectivist culture, n = 67) as a case study, we investigated: (1) which of the commonly researched UX design attributes (perceived aesthetics, perceived usability, perceived credibility and perceived usefulness) have the strongest influence on users' intention to use a fitness application; (2) the moderating effect of culture; and (3) how perceived persuasiveness mediates the direct effect of perceived usefulness on the intention to use a fitness application. The results of our path analysis show that, regardless of culture, perceived usefulness and perceived aesthetics are the strongest determinants of users' intention to use a fitness application, with perceived usefulness being stronger in the collectivist culture than in the individualist culture. Secondly, our results show that perceived persuasiveness partially mediates the effect of perceived usefulness on intention to use for the individualist culture, but not for the collectivist culture. Hence, we recommend that designers should invest more in improving functionality (utilitarian benefit) and aesthetics (hedonic benefit) than other UX design attributes such as credibility and usability. However, for the collectivist culture, designers should focus more on usefulness than aesthetics. On the other hand, for the individualist culture, designers should strike a balance between usefulness and aesthetics. Our main contribution is that, our study, to the best of our knowledge, is the first to investigate the moderating effect of culture using subjects from North America and Africa (an understudied population) as a case study.